HUBUNGAN PENGETAHUAN DAN SIKAP TENAGA KESEHATAN DENGAN PENCAPAIAN TARGET CAKUPAN PENEMUAN KASUS TB ANAK DI WILAYAH KERJA DINAS KESEHATAN KOTA DEPOK - Salma Destika Rafidah (2020)
The discovery of pulmonary TB cases conducted in Depok may help prevent the occurrence of pulmonary TB transmission, especially for children. The TB control program implementation requires health workers that have competent knowledge and professional attitude. This research aim is to know the relationship of health worker's knowledge and attitude with target achievement of children's TB case discovery in Depok Health Office working area. The research method used a cross-sectional approach. Samples totaled 30 people, used a simple random sampling technique. Data analysis used chi-square test. The results of the study obtained as many as 80% of subjects had good knowledge, and 73.3% of subjects had good attitudes. The results of the chi square test showed a relationship between knowledge (p = 0.001) and attitudes (p = 0.007) of health workers with the achievement of coverage targets of Children TB discovery.